Mutational Hypersensitivity of a Gene Regulatory Protein: Saccharomyces cerevisiae Gal80p - Melcher, Karsten (Copyright © 2005 by the Genetics Society of America, 2005)
The inhibitor of galactose catabolic (GAL) gene expression in Saccharomyces cerevisiae, Gal80p, interacts with the activator Gal4p and the signal transducer Gal3p and self-associates. Selection for loss of Gal80p inhibitor function yielded gal80 mutants at an extremely high rate. Out of these, 21 nonoverlapping point mutants were identified; each were due to a single-amino-acid exchange in conserved residues. Semiquantitative biochemical analysis of the corresponding mutant proteins revealed that each of the 21 amino acid alterations caused simultaneous defects in every single protein-protein interaction and in Gal80's structural integrity. Thus, Gal80 provides an unprecedented example for a protein's structural sensitivity to minimal sequence alterations.